Impact of Corporate Governance on Perceived Performance of Manufacturing Industries of Nepal (Orchid Academia Siraha, 2024)
The aim of this research is to examine how corporate governance affects the perceived performance of manufacturing industries in Nepal. The study utilized a descriptive and causal comparative research approach. Key aspects of corporate governance identified include commitment to governance, transparency and disclosure, and the structure and operation of the board. Meanwhile, productivity and profitability were treated as control variables, both serving as dependent variables for assessing industry performance. The analysis encompassed all 19 manufacturing industries listed on the Nepal Stock Exchange. To achieve the study's objectives, judgmental sampling was employed from a non-probability sampling method, while purposive sampling was used to choose respondents who completed the questionnaires. Out of the total 19 industries, only five were selected for the sample. Participants included selected financial and marketing professionals from these companies, with 100 respondents from the five industries completing the questionnaire. The data collected were analyzed through a multiple linear regression model. The results demonstrated that strong corporate governance positively impacts a company's performance.